Aggregate model of health care expenditure in Singapore based on historical records - Seng, Lee Huang. (2008)
In this project an aggregate model of health expenditure in Singapore is developed using regression method based on the principle of ordinary least square. The results indicate that the key determinants of health care spending are: 1) gross domestic product per capita 2) percentage of government health care expenditure to gross domestic product and 3) Medisave scheme. The gross domestic product contributes 68% and the percentage of government health expenditure to gross domestic product contributes 31% and the Medisave scheme contributes 1% to the growth in healthcare expenditure. Factors like the ratio of doctor to population and proportion of aging population do not significantly affect health care expenditures.